Rectal leiomyoma, a rare entity - Tagore Sunkara; Eric Omar Then; Andrea Culliford; Vinaya Gaduputi (Clinics and Practice, 2018)
Rectal tumors are often encountered as an incidental finding on screening colonoscopy. As per the World Health Organization, they are categorized according to their histologic appearance. These include epithelial tumors, mesenchymal tumors and lymphomas. Of interest, in our case, are mesenchymal tumors. These are sub-classified into leiomyomas and gastrointestinal stromal tumors. Our case is a 33-year old male who was diagnosed with a rectal leiomyoma. The uncommon incidence and subsequent management of a rectal leiomyoma in a male, make this case worthy for literature review.